EFECTOS DE FITONUTRIENTES A BASE DE CÁSCARA DE CACAO EN PLANTAS DE PIMIENTO (Capsicum annuum L.) - Carpio Mora, Erika Paulina (2023)
The research was carried out under a greenhouse on the grounds of the “La María” University Campus, premises of the State Technical University of Quevedo, located at kilometer 7 ½. From the Quevedo El Empalme road, Canton Mocache, Province of Los Ríos, whose geographical location is 1° 3'18” south latitude and 79° 25' 24'' west longitude, with the objective of evaluating the effect of phytonutrients based on cocoa shells on pepper plants (Capsicum annuum L.) applied to the soil as organic fertilization, with a total of 4 treatments, each with 5 repetitions using a Complementary Random Design.